Phosphorylation-Dependent Pin1 Isomerization of ATR: Its Role in Regulating ATR’s Anti-apoptotic Function at Mitochondria, and the Implications in Cancer - Makinwa, Yetunde; Musich, Phillip R.; Zou, Yue (Frontiers in Cell and Developmental Biology, 2020)
Peptidyl-prolyl isomerization is an important post-translational modification of protein because proline is the only amino acid that can stably exist as cis and trans, while other amino acids are in the trans conformation in protein backbones. This makes prolyl isomerization a unique mechanism for cells to control many cellular processes. Isomerization is a rate-limiting process that requires a peptidyl-prolyl cis/trans isomerase (PPIase) to overcome the energy barrier between cis and trans isomeric forms. Pin1, a key PPIase in the cell, recognizes a phosphorylated Ser/Thr-Pro motif to catalyze peptidyl-prolyl isomerization in proteins. The significance of the phosphorylation-dependent Pin1 activity was recently highlighted for isomerization of ATR (ataxia telangiectasia- and Rad3-related). ATR, a PIKK protein kinase, plays a crucial role in DNA damage responses (DDR) by phosphorylating hundreds of proteins. ATR can form cis or trans isomers in the cytoplasm depending on Pin1 which isomerizes cis-ATR to trans-ATR. Trans-ATR functions primarily in the nucleus. The cis-ATR, containing an exposed BH3 domain, is anti-apoptotic at mitochondria by binding to tBid, preventing activation of pro-apoptotic Bax. Given the roles of apoptosis in many human diseases, particularly cancer, we propose that cytoplasmic cis-ATR enables cells to evade apoptosis, thus addicting cancer cells to cis-ATR formation for survival. But in normal DDR, a predominance of trans-ATR in the nucleus coordinates with a minimal level of cytoplasmic cis-ATR to promote DNA repair while preventing cell death; however, cells can die when DNA repair fails. Therefore, a delicate balance/equilibrium of the levels of cis- and trans-ATR is required to ensure the cellular homeostasis. In this review, we make a case that this anti-apoptotic role of cis-ATR supports oncogenesis, while Pin1 that drives the formation of trans-ATR suppresses tumor growth. We offer a potential, novel target that can be specifically targeted in cancer cells, without killing normal cells, to significantly reduce the adverse effects usually seen in cancer treatment. We also raise important issues regarding the roles of phosphorylation-dependent Pin1 isomerization of ATR in diseases and propose areas of future studies that would shed more understanding on this important cellular mechanism.